2023
DOI: 10.3389/fphar.2023.1090526
|View full text |Cite
|
Sign up to set email alerts
|

Acori Tatarinowii Rhizoma: A comprehensive review of its chemical composition, pharmacology, pharmacokinetics and toxicity

Abstract: Acori Tatarinowii Rhizoma (ATR, Shi Chang Pu in Chinese), a natural product with multiple targets in various diseases. This review provides the comprehensive summary of the chemical composition, pharmacological effects, pharmacokinetics parameters and toxicity of ATR. The results indicated that ATR possesses a wide spectrum of chemical composition, including volatile oil, terpenoids, organic acids, flavonoids, amino acids, lignin, carbohydrates and so on. Accumulating evidence from various studies has shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Antioxidants with antiinflammatory effects exert inhibitory effects on the onset and progression of DR [41][42][43]. β-asarone, a type of volatile oil, exerts multiple pharmacological effects, including antioxidant and anti-inflammatory effects [19,20,44]. In addition to these pharmacological effects, β-asarone is also known for toxicological effects in hepatoma, mutagenic, and genotoxic action [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants with antiinflammatory effects exert inhibitory effects on the onset and progression of DR [41][42][43]. β-asarone, a type of volatile oil, exerts multiple pharmacological effects, including antioxidant and anti-inflammatory effects [19,20,44]. In addition to these pharmacological effects, β-asarone is also known for toxicological effects in hepatoma, mutagenic, and genotoxic action [20].…”
Section: Discussionmentioning
confidence: 99%
“…β-Asarone (cis-2,4,5-trimethoxy-1-allyl phenyl) is a volatile oil present in various herbal medicines, including Acorus tatarinowii Schott. It exerts various biological effects, including antioxidant, anti-inflammatory, and anti-cancer effects [19,20]. For example, β-asarone suppresses the production of pro-inflammatory mediators and cytokines by blocking the NF-κB signaling pathway and preventing the development of neuroinflammatory diseases [21].…”
Section: Introductionmentioning
confidence: 99%
“…They belong to the genus Acorus and have similar morphological characteristics in their aerial parts (i.e., leaves) and rhizomes [ 9 ]. Their rhizomes, Acorus tatarinowii rhizome (ATR) and Acorus gramineus rhizome (AGR), are widely used for amnesia in traditional Chinese medicine [ 10 , 11 , 12 ]; ATR is used in China, and AGR is used in Japan [ 9 ]. In contrast, their leaves, referred to as Acorus tatarinowii leaf (ATL) and Acorus gramineus leaf (AGL), are seldom used in traditional Chinese medicine and are usually discarded without their medicinal properties being known.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the rhizomes are treated as pharmaceuticals, whereas the leaves are regarded as non-pharmaceuticals (i.e., treatable as foodstuffs). The rhizomes contain various ingredients [ 10 , 11 , 12 ], and α-asarone and β-asarone are the main active components that have been shown to improve cognition in mice and rats [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. We speculated that the leaves may contain some active ingredients similar to the rhizomes; therefore, we compared their effects on mouse cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Ginseng Radix et Rhizoma is a great tonic medicine for benefiting Qi and invigorating vitality, with pharmacological effects which include improving learning and memory, stimulating the central nervous system, anti-tumor effects, and strengthening the immune system ( Shi et al, 2013 ; Jiang et al, 2019 ; Yu et al, 2020 ). Additionally, studies have reported that Acori Tatarinowii Rhizoma has various pharmacological effects, including antioxidant and anti-depression properties, protecting nerve cells, alleviation of learning and memory impairment, and anti-myocardial ischemia ( Zhang et al, 2015 ; Wen et al, 2023 ). In addition to regulating gut microbiota, Poria cocos has anti-inflammatory and antioxidant pharmacological activities in treating diseases ( Fang et al, 2021 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%